On long decays of electrons in the vicinity of the slot region observed by HEO3. Issue 1 (29th January 2015) - Ripoll, J.‐F.; Chen, Y.; Fennell, J. F.; Friedel, R. H. W.
Abstract Long decay periods of electron counts, which follow abrupt rises and last from weeks to months, have been observed by the HEO3 spacecraft in the vicinity of the slot region between the years 1998 and 2007. During the most stable decay periods as selected, e‐folding timescales are extracted and statistically analyzed from observations as a function of L‐shell and electron energy. A challenge is to reproduce the observed timescales from simulations of pitch angle diffusion by three acting waves—the plasmaspheric hiss, lightning‐generated whistlers, and VLF transmitter waves. We perform full numerical simulations to accurately compute electron lifetimes. We choose to use the method and wave parameters proposed by Abel and Thorne in 1998 with the goal to assess whether they can reproduce lifetimes extracted from HEO observations. We show how hiss dominantly affect high energy electrons (E > 2 MeV) for L in [2, 3.5] and VLF transmitter waves control residency times of low energy electrons (<0.4 MeV) around L = 2. These interactions induce characteristic shapes of the lifetime profiles that will be discussed. We show how the wave amplitudes can be adjusted for the particular energy particles that are dominantly affected by one wave type only. Using these amplitudes, mean HEO lifetimes are reproduced within a factor 2 to 5. VLF occurrence rates and hiss amplitude turn out significantly higher than those proposed by Abel and Thorne. The wide energy response of the sensors complicates the analysis because it blurs the electron lifetime dependence on energy, increases the overall lifetimes, and reduces the differences between the different channel lifetimes. In particular, our simulations suggest the flux measured by an integrated energy sensor aboard HEO has a variable slope, i.e., a variable lifetime, during 10–20 days in our data, due to the faster decay of the low residency time particles while slower decaying particles control the steady decay. It can explain some of the multi‐slopes decays observed by HEO. HEO electron long decay timescales are also compared to the timescales previously observed from Solar Anomalous and Magnetospheric Particle Explorer (SAMPEX) and Combined Release and Radiation Effects Satellite (CRRES) with differences attributed to factors such as instrument characteristic and different satellite orbits.